2007
DOI: 10.1158/0008-5472.can-07-0794
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Indole-3-Carbinol–Derived Antitumor Agent with Pleiotropic Effects on Multiple Signaling Pathways in Prostate Cancer Cells

Abstract: Indole-3-carbinol has emerged as a promising chemopreventive agent due to its in vivo efficacy in various animal models. However, indole-3-carbinol exhibits weak antiproliferative potency and is unstable in acidic milieu. Thus, this study was aimed at exploiting indole-3-carbinol to develop potent antitumor agents with improved chemical stability. This effort culminated in OSU-A9 {[1-(4-chloro-3-nitrobenzenesulfonyl)-1H-indol-3-yl]-methanol}, which is resistant to acid-catalyzed condensation, and exhibits 100-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 39 publications
(42 reference statements)
3
60
0
1
Order By: Relevance
“…8,10,11) Our results also showed that, against HUVECs, I3C failed to affect cell growth at the concentration which was sufficient to inhibit tube formation and induce apoptosis in the tube-forming endothelial cells. Tube-forming endothelial cells have been reported to function and express genes/proteins that are closer to those observed in vivo than dishcultured endothelial cells.…”
mentioning
confidence: 50%
“…8,10,11) Our results also showed that, against HUVECs, I3C failed to affect cell growth at the concentration which was sufficient to inhibit tube formation and induce apoptosis in the tube-forming endothelial cells. Tube-forming endothelial cells have been reported to function and express genes/proteins that are closer to those observed in vivo than dishcultured endothelial cells.…”
mentioning
confidence: 50%
“…The overexpression of Survivin in these tumors may be due to an autoregulation of its own synthesis or a result of a loss of control over Stat3 (by GRIM-19), which is known to induce Survivin. 32 Similarly, RT-PCR and Western blot results also showed that Survivin was highly upregulated in PCa tissue and prostatic DU145 cells while GRIM-19 was severely depressed (P,0.01) (Supplementary Figure 1b-e). The expression levels of Survivin and GRIM-19 in tumors were significantly different from those found in normal tissues (Supplementary Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 71%
“…Recovery was carried out by known cabbage samples spiked with indole-3-carbinol at concentrations of 10 . The determination of detection limits (LODs) and quantification limits (LOQs) was performed by analysis of the decrease in the concentration of the standard solutions.…”
Section: Methods Validationmentioning
confidence: 99%
“…Epidemiological and clinical studies suggest that indole-3-carbinol is a potential agent in blocking tumour initiation, oestrogen metabolism, inhibition of cell proliferation and induction of apoptosis [3,4,5,6,7]. So far, many studies have shown indole-3-carbinol is a bioactive component that plays an important anti-cancer role against breast [8], liver [9], prostate [10], lung and colon cancers [11,12]. Thus, indole-3-carbinol has been widely studied and has proved to be a potentially useful agent in cancer prevention.…”
Section: Introductionmentioning
confidence: 99%